Globalisation and its Impact on the Journal Collections of Research Libraries in Australia: A Health Library's Perspective. Issue 1 (2nd January 2018) - Purnell, Margaret
Abstract: Globalisation has a direct impact on the collection development budgets of Australian research libraries. Electronic journal subscriptions make up a significant proportion of these budgets and are influenced by factors such as: the value of the Australian dollar, the domination of multinational publishing companies and available library funding. Open access publishing has developed in response to the escalating costs and restricted access of subscription journals. This paper focuses on these issues from the perspective of the Northern Territory Department of Health Library. Research libraries require sustained financial support from federal, state and territory governments to maintain the electronic resources their clients need.